Prometeo: Geschichtskonzeptionen in Luigi Nonos Hörtragödie - Jeschke, Lydia (Stuttgart Steiner, 1997)
This major, central late work by one of the most important composers of the 20th century is comprehensively examined here for the first time on the basis of the entire archive material for Prometeo. The Italian composer's innovative concept and his examination of the ancient subject is interpreted as a cultural-critical continuation of the Prometheus myth at the end of the 20th century, but also as the search for possibilities of a specifically musical reflection of history and historiography. On the basis of the sketch material, which has been made accessible for the first time, the composition becomes the subject of detailed analyses and fundamental reflections on contemporary compositional techniques. The study focuses on the disposition of the performance space, the multidimensional conception of musical time and the compositional handling of historical material. "Nevertheless, this is gripping, unusual music that makes demands. We have Lydia Jeschke to thank because we know much more and much more detail about it." Musiktheorie. (Translated with Deepl.com)
Originally presented as the author's thesis (doctoral)--Universität Freiburg im Breisgau, 1996.
Includes bibliographical references (p. [253]-262)
Keywords: Nono, Luigi -- 1924-1990; Musical analysis; Sound; Music philosophy and esthetics